Prosocial Behavioral Values in Islamic Education Materials for Seventh-Grade Students: A Content Analysis of the 2013 Curriculum Textbook - Nanang Eka Saputra (JPI: Jurnal Pustaka Indonesia, 2023)
The increasing influence of globalization has fostered individualism among young generations, often resulting in declining self-discipline, reduced empathy, and weakened social cohesion. This study investigates the representation of prosocial behavioral values embedded in the official Islamic Education and Character Education textbook for seventh-grade students (second semester), published by Indonesia’s Ministry of Education and Culture (Kurikulum 2013). Employing library research and qualitative content analysis, the study examined selected chapters of the revised 2017 edition. Findings indicate that the textbook incorporates diverse prosocial values, including empathy, altruism, generosity, cooperation, honesty, friendship, helping behavior, sacrifice, and charitable giving. These values are illustrated through narratives, Qur’anic verses, and Hadith that highlight moral exemplars such as Prophet Muhammad, Abu Bakr, and Umar ibn Khattab. The integration of prosocial values in Islamic education materials reflects the pedagogical intent to balance cognitive, affective, and moral development. However, the analysis also reveals limitations in the depth of contextualization, suggesting a need for more explicit strategies to connect values with students’ everyday realities. This study contributes to the discourse on value-based education and provides insights for curriculum developers, educators, and policymakers seeking to strengthen prosocial orientations among adolescents.